Letter from Carl D. Duncan to Patricia Whiting, April 21, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan explains himself over an apparent misunderstanding and asks Whiting to be comfortable in asking him for help.